Alcohol Scale, Internet Addiction Scale, E-Victim Scale and E-Bullying Scale in Cigarette Addicted University Students - Çetin, Ebru; Emiral, Emrah; Cantürk, Nergis; Dağalp, Rukiye (Technium Social Sciences Journal, 2021)
The present study aims to determine the relevant variables for the scores obtained from alcohol addiction, internet addiction, e-bullying, and e-victimization scales of smoking-addictive university students and to investigate the possible correlations between the scales. The study group consists of 300 students who declared that they smoked at least one cigarette every day for the last 6 months. The data were collected with a face-to-face interview method. The form used in the study consisted of items belonging to alcohol addiction, Internet addiction, e-bully, and e-victimization scales. According to the Alcohol Scale, 61.3% of the participants were in the non-addictive group, and 63.3% were in the risk group according to the Internet addiction scale. 2.7% of the participants were e-bullies and 2.3% were e-victims. There was no correlation between the Alcohol Addiction and the Internet Addiction scores of the participants (p>0.05), while a weak positive correlation was detected between the e-bullying and e-victimization scores (for each; p <0.05). A positively weak correlation was found between the Internet Addiction score and e-bullying and e-victimization scores (p <0.05 for each). Our results suggested that students with any type of addiction have a higher risk for other types of addictions (substance-behavioral) as well.